2020
DOI: 10.1007/s12630-020-01865-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an anesthesia perioperative surgical home for total knee and hip arthroplasty at a Veterans Affairs Hospital: a quality improvement before-and-after cohort study

Abstract: Background A perioperative surgical home, the Anesthesia Perioperative Care Service (APCS), was created to execute enhanced recovery after surgery pathways for total knee and total hip arthroplasty patients at the Tennessee Valley Health System Nashville VA Medical Center. We hypothesized that the APCS would be associated with reduced length of stay, in-hospital and post-discharge opioid exposure, costs, and hospital readmissions. Methods Data were collected for all patients admitted to the Nashville VA Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Paradoxically, in their analysis 90 days after hip and knee arthroplasty, Jørgensen et al found that fall-related hospital readmissions were due to physical activity and extrinsic factors other than surgery because of patient success and intent to return to a normal level of activity [ 24 ]. As emerged from all of the studies examined in this review, in turn, all of these interventions reduce the LOS as patients could be discharged sooner without increasing the risk of complications (References [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, in their analysis 90 days after hip and knee arthroplasty, Jørgensen et al found that fall-related hospital readmissions were due to physical activity and extrinsic factors other than surgery because of patient success and intent to return to a normal level of activity [ 24 ]. As emerged from all of the studies examined in this review, in turn, all of these interventions reduce the LOS as patients could be discharged sooner without increasing the risk of complications (References [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
“…Designation of positive, neutral and negative outcome for each examined study. (References [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ...…”
mentioning
confidence: 99%
“…The study limitations include not having all the important factors for the analysis like patient's age, gender, Body Mass Index (BMI), and ASA score. Past studies have found these confounders were associated with the orthopedic surgical outcomes including LOS, discharge disposition, and 90-days readmission (Alvis et al, 2021;Duplantier et al, 2015;Garson et al, 2014;Kim et al, 2017;Kim et al, 2019;Powell et al, 2017;Qiu et al, 2016). Second, the study was only able to compare a five-month duration (November to April) for both cohorts.…”
Section: Discussionmentioning
confidence: 95%
“…In both evaluations, the LOS was shorter in the PSH cohort compared to the control cohorts (median PSH = 34 h, C1-PSH = 53 h, C2-PSH = 35 h)[ 14 , 33 , 34 ]. Although there was no statistical difference in LOS between the PSH and the C2-PSH cohort in the unadjusted analysis, the LOS was significantly shorter in the PSH cohort (10% shorter) in the adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline characteristics were compared with variables including patient age, gender, body mass index (BMI), ASA score (Class 1, 2, 3, or 4), procedure type (THA, TKA, and TSA) and insurance type (private or public payer). These variables were included in the baseline characteristics and in the analysis, as they were found to be potential confounders at PSH implemented hospitals with the surgical outcomes LOS, discharge disposition, and 90-d readmission[ 14 , 16 , 24 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%